Summing Up on the Australian Case for Protection - Samuelson, Paul A. (Quarterly Journal of Economics, 1981)
Journal Article Summing up on the Australian Case for Protection Get access Paul A. Samuelson Paul A. Samuelson Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 96, Issue 1, February 1981, Pages 147–160, https://doi.org/10.2307/2936145 Published: 01 February 1981